THE INTERRELATIONSHIP OF LANGUAGE AND THE BRAIN AND LANGUAGE DISORDERS IN AUGMENTATIVE AND ALTERNATIVE COMMUNICATION (AAC): FINDINGS FROM A SYSTEMATIC REVIEW OF THE LITERATURE - Garnace, Xenia (PEOPLE: International Journal of Social Sciences, 2018)
This study presents a systematic literature review focusing on the Interrelationship of Language and the Brain and Language Disorders in Augmentative and Alternative Communication (AAC) based on a number of published researches in several refereed international journals available in various online databases. A repertory grid was utilized to plot the responses to the research questions posted. The data on the grid were analyzed to be able to identify the various gaps in the researches conducted. Consequently, this study yields the following concepts: the Role of Assistive Technology and Mediation, Interventions in AAC, and Focus on AAC Outcomes. It is concluded that these concepts should form part of the compendia to be used by language teachers, especially those specializing in psycholinguistics and AAC. Finally, the paper presents suggestions for further research into AAC and psycholinguistics per se.